2014
DOI: 10.1016/j.apradiso.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Online in vivo dosimetry in high dose rate prostate brchytherapy with MOSkin detectors: In phantom feasibility study

Abstract: MOSkin detectors were studied to perform real-time in vivo dose measurements in high dose rate prostate brachytherapy. Measurements were performed inside an urethral catheter in a gel phantom simulating a real prostate implant. Measured and expected doses were compared and the discrepancy was found to be within 8.9% and 3.8% for single MOSkin and dual-MOSkin configurations, respectively. Results show that dualMOSkin detectors can be profitably adopted in prostate brachytherapy treatments to perform real-time i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 20 publications
4
18
0
Order By: Relevance
“…The corresponding detector sensitivities were 2.43mV/cGy and of 2.49mV/cGy, respectively. Detector sensitivities were similar to those of the MOSkin detectors from other batches which were 2.17mV/cGy as reported by Qi et al (2012) and of 2.63mV/cGy as reported in Gambarini et al (2014). Differences between these values might be due to intrinsic differences of the structural and packaging materials between each single dosimeter and to a small sensitivity reduction that might be observed over the entire life time of the detectors.…”
Section: Moskin Calibration With the Ir-192 Brachytherapy Sourcesupporting
confidence: 62%
See 1 more Smart Citation
“…The corresponding detector sensitivities were 2.43mV/cGy and of 2.49mV/cGy, respectively. Detector sensitivities were similar to those of the MOSkin detectors from other batches which were 2.17mV/cGy as reported by Qi et al (2012) and of 2.63mV/cGy as reported in Gambarini et al (2014). Differences between these values might be due to intrinsic differences of the structural and packaging materials between each single dosimeter and to a small sensitivity reduction that might be observed over the entire life time of the detectors.…”
Section: Moskin Calibration With the Ir-192 Brachytherapy Sourcesupporting
confidence: 62%
“…The choice was taken in accordance to many other studies reported in literature, such as Lambert et al (2006), Therriault-Proulx et al (2011) and Gambarini et al (2014). In fact, factors implemented in the TPS are those tabulated in Daskalov et al (1998) and are obtained by means of Monte Carlo photon transport code knowing the characteristics of the specific source model (i.e., mHDR-v2).…”
Section: Moskin Calibration With the Ir-192 Brachytherapy Sourcementioning
confidence: 99%
“…Prostate cancer is the second most commonly diagnosed cancer (after non-melanoma skin cancer) and one of the leading causes of cancer death among males in Australia and worldwide (Gambarini et al, 2014). In 2017, it is estimated that there will be 16,665 new cases of prostate cancer and 3,452 deaths in Australia; in the United States, the respective figures are 161,360 and 26,730 (AIHW National Mortality Database, 2017;Siegel et al, 2015;The American Cancer Society, 2017;Cancer Research UK, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It should be emphasized that a small outer diameter of the dosemeter probe and a small detector volume are required in order to allow for IVD at the surface of the catheter into which the probe is incorporated. For this reason, several kinds of MOSFETs 46,67 and fibre-coupled dosemeters 18,19,75,76 are ideal, in contrast to most commercial diodes that have bulky packaging and thus do not facilitate a dosimetry point near the surface of the OAR. The MOSkin detector recently introduced by the Centre for Medical Radiation Physics, University of Wollongong, Wollongong, NSW, Australia, is particularly suitable in this case, given its 0.07-mm water equivalent depth of sensitive volume.…”
Section: Dosemeter Placement Toolsmentioning
confidence: 99%
“…The small sensitive volume allows for dosimetry in steep dose gradients as well as cases of electronic disequilibrium, which are common conditions in BT. It also allows for the construction of small dosemeter probes with approximately 1.3-mm outer diameters that can fit inside small catheters in or near the tumour region, and therefore facilitates IVD inside urethral catheters 15,46,[65][66][67] and inside nasopharyngeal applicators. 68 Common disadvantages of semiconductor dosemeters are temperature and energy dependences in radiation fields.…”
Section: Semiconductor Dosimetrymentioning
confidence: 99%